Antihypertensive Medication Adherence and Risk of Cardiovascular Disease Among Older Adults: A Population‐Based Cohort Study. Issue 6 (June 2017) - Yang, Quanhe; Chang, Anping; Ritchey, Matthew D.; Loustalot, Fleetwood
Abstract : Background: Antihypertension medication (antihypertensive) adherence lowers risk of cardiovascular disease (CVD); few studies have examined this association among older adults. Methods and Results: We assessed this association among Medicare fee‐for‐service beneficiaries aged 66 to 79 years who were newly diagnosed with hypertension and initiated on antihypertensives in 2008–2009 (n=155 597). We calculated proportion of days covered (PDC) during follow‐up, using proportional subdistribution hazard models, to examine association between antihypertensive adherence and a composite CVD outcomes, including first incident of fatal/nonfatal acute myocardial infarction, ischemic heart disease, stroke/transient ischemic attack, and heart failure. During follow‐up (median 5.8 years and 798 621 person‐years), we documented 47 198 CVD events. Among beneficiaries, 60.8%, 30.3%, and 8.9% had PDC ≥80%, 40% to 79%, and <40%. Crude incidence of CVD events were 40.1 (95% CI, 40.0–40.1), 93.9 (93.8–93.9), and 98.1 (98.1–98.2) per 1000 person‐years for PDC ≥80%, 40% to 79%, and <40%, respectively. Adjusted hazard ratios for CVD events were 1.0 (<40% as reference), 1.0 (0.97–1.03) for 40% to 79%, and 0.44 (0.42–0.45) for ≥80% ( P <0.001). Dose‐response analysis suggested a nonlinear relationship between PDC and risk for CVD events with a protective effect of ≥80%. The pattern of associations between PDC and ischemic heart disease, stroke/transient ischemic attack, and heart failure were largely consistent as for CVD events and across different groups. Conclusions: Antihypertensive adherence was associated with a significantly lower risk of CVD events among older adults. There appeared to be a threshold effect in reducing CVD events at around PDC 80%, above which the risk for CVD reduced substantially.